Integration of dynamic problems of mechanics of deformable solids by generalized Runge - Kutta methods - Nemirovskii, Yuriy Vladimirovich; Yankovskii, Andrey Petrovich (Computational Continuum Mechanics, 2008)
The original numerical procedure of integration of initial-boundary problems of mechanics of deformable solids is developed based on a generalization of Runge - Kutta methods. The efficiency of the proposed numerical method is confirmed by numerous calculations of the elastic and non-elastic dynamics of homogeneous and composite thin-walled structures.